2020
DOI: 10.1111/mcn.12964
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality over time is associated with better development in rural Nepali children

Abstract: Developmental delays affect between 150 and 200 million children <5 years of age worldwide. Outside of diet supplement studies, relatively little is known about the relationships between diet quality and developmental status in resource‐poor settings. We examined associations between different aspects of dietary quality (dietary diversity score [DDS] and animal‐source food [ASF] consumption) and child development (assessed using the Ages and Stages Questionnaire‐3 [ASQ‐3]) among children whose families were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
(130 reference statements)
1
10
1
Order By: Relevance
“…We hypothesized that child and family diet quality would diminish during the pandemic, but that dairy animal ownership would buffer this decline. Prior to the pandemic, child and household diets were similar to what has been previously described in this area of Nepal [ 27 , 28 , 62 , 63 ], with low DDS and ASF consumption. Over the 21 months of the pandemic, both child and family diet quality declined.…”
Section: Discussionsupporting
confidence: 58%
“…We hypothesized that child and family diet quality would diminish during the pandemic, but that dairy animal ownership would buffer this decline. Prior to the pandemic, child and household diets were similar to what has been previously described in this area of Nepal [ 27 , 28 , 62 , 63 ], with low DDS and ASF consumption. Over the 21 months of the pandemic, both child and family diet quality declined.…”
Section: Discussionsupporting
confidence: 58%
“…We have previously reported on the relationship between minimum dietary diversity, consumption of ASFs, fruits and vegetables, cumulative DDS, and ASQ results in young children. 38,39 In the present small sample, however, we found a stronger and more consistent relationship between child developmental performance and ASF consumption than with DDS. We are unaware of other studies that have directly compared the relation of child development to ASF sum and DDS.…”
Section: Discussioncontrasting
confidence: 56%
“…This standardized screening instrument is used worldwide (including Nepal) to assess child development. 38,39,[51][52][53][54] Feasibility and construct validity in northern India 55,56 as well as in Nepal have recently been reported. 54,57 The test is scored by observation (or parent report) and consists of 30 age-specific items within 5 domains: communication (eg, at age 30 months, correctly naming pictures of items such as a ball, a hat), gross motor (able to jump with both feet leaving the ground at the same time), fine motor (able to string beads), problem-solving (identifying his/ her image in a mirror), and personal-social skills (able to put on a jacket or shirt independently).…”
Section: Child Developmental Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Ethiopia and the rest of the world showed several factors that would have increased IYCF practice indicators in general and dietary diversity in specific among children aged 6-23 months old. Increased maternal education, household monthly income, being urban resident, mothers' knowledge on dietary diversification and attending any growth monitoring programmes as well as cooking demonstration, proper and sufficient exposure to media, antenatal and postnatal care service utilisation, a household visit by health extension worker (HEW), husband involvement in IYCF programmes and mothers' decision-making ability and age of mother and child are some of the positively associated factors acquiring better and sufficient diet (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) . However, almost all of the studies attempted to find predictors (associated factors) of dietary diversity using maximum likelihood estimation that shows changes in the log odds of the dependent, not direct changes in the dependent itself.…”
Section: Introductionmentioning
confidence: 99%